2012
DOI: 10.1073/pnas.1209891109
|View full text |Cite
|
Sign up to set email alerts
|

Transition paths, diffusive processes, and preequilibria of protein folding

Abstract: Fundamental relationships between the thermodynamics and kinetics of protein folding were investigated using chain models of natural proteins with diverse folding rates by extensive comparisons between the distribution of conformations in thermodynamic equilibrium and the distribution of conformations sampled along folding trajectories. Consistent with theory and single-molecule experiment, duration of the folding transition paths exhibits only a weak correlation with overall folding time. Conformational distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 67 publications
(115 reference statements)
5
41
0
Order By: Relevance
“…Furthermore, Chan et al (Chan et al 2011) presented a set of coarse-grained models for real proteins that can successfully capture the experimental contact order-related folding rates. However, in the recent detailed simulation of the folding transition paths of a similar set of model proteins (mentioned above in section A-d), Zhang and Chan (2013) found that the transition paths of folding have more non-local contact than typical conformations in the folding quasipreequilibrium with the same number of native contacts. Fersht (Fersht 2000) also asserts that the correlation cannot exclude the role of some tertiary interactions in formation of the extended nucleus.…”
Section: O'neill Et Al (O'neill and Robert Matthews 2000)mentioning
confidence: 95%
See 1 more Smart Citation
“…Furthermore, Chan et al (Chan et al 2011) presented a set of coarse-grained models for real proteins that can successfully capture the experimental contact order-related folding rates. However, in the recent detailed simulation of the folding transition paths of a similar set of model proteins (mentioned above in section A-d), Zhang and Chan (2013) found that the transition paths of folding have more non-local contact than typical conformations in the folding quasipreequilibrium with the same number of native contacts. Fersht (Fersht 2000) also asserts that the correlation cannot exclude the role of some tertiary interactions in formation of the extended nucleus.…”
Section: O'neill Et Al (O'neill and Robert Matthews 2000)mentioning
confidence: 95%
“…Juraszky et al (Juraszek and Bolhuis 2006) found that in the folding of the small protein, i.e., the WW cage, 80 % of the pathways are initiated by NLI while secondary structures appear later. Zhang and Chan (2013) performed explicitchain simulations using coarse grained chain models of natural proteins and computed the transient distributions of conformations sampled along the trajectories of many molecules. They found that conformations in the initial phases of the faster pathways were enriched with NLIs.…”
Section: O'neill Et Al (O'neill and Robert Matthews 2000)mentioning
confidence: 99%
“…The problem of correctly discounting erroneous crossing events makes TST ill-suited for systems with highly diffusive dynamics (high entropic barriers) where recrossing happens many times during a single reactive transition [83,84]. Kramers' theory, which is related to TST and can be derived from variational TST in the diffusion limit [85], provides a scheme for deriving rate expressions under the assumption of Langevin dynamics along a suitable reaction coordinate.…”
Section: Rate Theoriesmentioning
confidence: 99%
“…The experimental advances created theoretical interest in transition paths and led to intense simulation activities [14][15][16] as well as the development of analytic approaches [5,17,18]. In this work, we present a theoretical framework for transition paths involving a combination of the backward Fokker-Planck equation, the forward Fokker-Planck equation, and the renewal equation approach, and use it to derive the mean shape of transition paths.…”
Section: Introductionmentioning
confidence: 99%